2013
DOI: 10.4028/www.scientific.net/kem.554-557.1992
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the BTA Deep Drilling Process through a Quantitative and Qualitative Analysis of the Chip Formation Process

Abstract: This paper deals with the analysis of the cutting process in the BTA (Boring Trepanning Association) deep hole drilling. The process is a major technique of drilling when the machining with a conventional tool is not possible. Poor training and/or poor chips evacuation often cause a temperature rise and excessive wear detrimental to the tool life and the dimensional stability of machined parts. The process is relatively not explored enough, because it is difficult to instrument experimental tests (measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The BTA deep drilling is used in numerous engineering areas, such as aeronautics [13], naval [14], automotive [15], nuclear and energy [16]. The research on BTA drilling mainly focuses on the following aspects, such as the role of guide pads [17,18], the vibrations occurring during machining [19], the chip formation process [20] and cutting force acting on the BTA drill [21]. Furthermore, a growing number of studies have concluded that the machined surface integrity (surface morphology, surface roughness [22], microstructure evolution [23,24], microhardness [25] and so on) of components signi cantly affects their integrity [26].…”
Section: Introductionmentioning
confidence: 99%
“…The BTA deep drilling is used in numerous engineering areas, such as aeronautics [13], naval [14], automotive [15], nuclear and energy [16]. The research on BTA drilling mainly focuses on the following aspects, such as the role of guide pads [17,18], the vibrations occurring during machining [19], the chip formation process [20] and cutting force acting on the BTA drill [21]. Furthermore, a growing number of studies have concluded that the machined surface integrity (surface morphology, surface roughness [22], microstructure evolution [23,24], microhardness [25] and so on) of components signi cantly affects their integrity [26].…”
Section: Introductionmentioning
confidence: 99%
“…The BTA deep drilling is used in numerous engineering areas, such as aeronautics [13], naval [14], automotive [15], nuclear and energy [16]. The research on BTA drilling mainly focuses on the following aspects, such as the role of guide pads [17,18], the vibrations occurring during machining [19], the chip formation process [20] and cutting force acting on the BTA drill [21]. Furthermore, a growing number of studies have concluded that the machined surface integrity (surface morphology, surface roughness [22], microstructure evolution [23,24], microhardness [25] and so on) of components signi cantly affects their integrity [26].…”
Section: Introductionmentioning
confidence: 99%